I Beam for civil construction fabricated with fast growing plantation wood in Costa Rica - Tenorio-Monge, Carolina (2014)
Recently, the timber market in Costa Rica has been supplied with fast growing trees from forest plantations. However, there are some problems relationed to design and development of high technology products. In order to introduce the forest plantations woods in the market, the main objective of this study was to determinate the design stress (bending, shear and bending stiffness) from I-beams fabricated with Gmelina arborea wood using lumber for the flanges and 12 mm plywood for web. Three types of profiles were developed (24 cm, 16 cm and 10 cm in high) and two quality types (A and B). The results showed that the design stress varied from 60 to 147 kg/cm2 in bending stress and from 42 to 92 kg/cm2 in shear stress. The I-beams of 10 cm and A quality showed the highest bending and shear stress, followed by I-beams of the 24 cm and 16 cm. With regard to bending stiffness, the profile of I-beams of 24 cm is those with the highest value, with 302787437.1 kg-cm2, followed by the profiles of 16 cm and 10 cm. By demonstrating the use of the I-beams in flooring systems, it had been observed that the quality A beams are those that produce optimal lengths for the market. For roofing systems, a quality classification of the beams no effect on the allowable length.